Anna Maria Evans papers - Evans, Anna Maria, approximately 1828-approximately 1905.
Chiefly correspondence documenting the life of women in Quaker (Society of Friends) communities and reflecting Quaker involvement in the abolition of slavery, the Civil War, women's rights, religious tolerance, revivalist meetings, and temperance. Includes letters (circa 1850-1905) between Evans and and her friend, Roanna Fox Bean, who lived at various times in Iowa, Minnesota, and California. Other letters are from wives of Quaker missionaries or officials in the United States and overseas, including Gertrude Whittier Cartland, M.H. Morrell, and Susan T. Thompson. Also includes letters of Evans's daughter, Flora Anna Evans, who was active in religious organizations in Boston, Mass., that describe revivalist meetings led by Dwight Lyman Moody and Sam P. Jones.
Member of the Society of Friends who operated an orchard near Rochester, N.H., with her husband, Thomas Evans. Born Anna Maria Roberts.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Bean, Roanna Fox -- Correspondence; Cartland, Gertrude Whittier, -- 1822-1911 -- Correspondence; Evans, Flora Anna -- Correspondence; Evans, Thomas, -- -1902.; Jones, Sam P. -- 1847-1906.; Moody, Dwight Lyman, -- 1837-1899.; Morrell, M. H. -- Correspondence; Thompson, Susan T. -- Correspondence; Evangelistic work -- United States; Missionaries; Religious institutions -- Massachusetts -- Boston; Religious tolerance -- Society of Friends; Slavery -- United States; Society of Friends; Society of Friends -- Missions; Temperance -- Religious aspects -- Society of Friends; Women's rights -- Religious aspects -- Society of Friends; California -- Social life and customs; Iowa -- Social life and customs; Minnesota -- Social life and customs; Rochester (N.H.) -- Social life and customs; United States -- History -- Civil War, 1861-1865.; Quakers